Pedagogical Competence of Arabic Language Lecturers at Islamic University - Budi Santoso Wibowo (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract This study aims to explore more deeply about the pedagogical competence of Arabic language lecturers at Islamic University. This study used a descriptive qualitative approach with case study type of research. For data collection, the researcher used three data collection techniques, namely: (1) observation, (2) in-depth interview, and (3) documentation study. The results of this study lead to a conclusion that the pedagogical competencies of Arabic language lecturers are: firstly, the ability to understand the characteristics of students. The strategies are: (1) introduction at the beginning of the lecture, (2) daily in-depth observations, and (3) placement tests (ikhtibār al-tashnīf). This understanding of student characteristics helps lecturers in optimizing the achievement of learning objectives, planning, implementing and evaluating learning. Secondly, the ability to utilize technology in learning. Two of the technology-based infrastructure used by lecturers are the Arabic Language Laboratory and the Computer and Multimedia Laboratory. In addition, lecturers also utilize technology in the form of social media as an alternative media in learning Arabic, namely: (1) Instagram, (2) Youtube, (3) Facebook, (4) Zoom Cloud Meeting, and (5) WhatsApp Group. The benefits of utilizing technology for learning Arabic are : assisting and simplifying the learning process, making learning more flexible both in terms of time and place, making students think creatively, growing self-confidence for students, assisting to improve the four language skills, and making students able to wisely utilize technology, especially technology in the form of social media. Researchers hope that with this research, Arabic language lecturers can understand better the characteristics of their students and can utilize technology in learning, including alternative media in learning Arabic, that is technology in the form of social media. Keywords: Pedagogical Competence, Arabic Lecturer, Islamic University